Die reformierte Gründungsförderung für Arbeitslose: Chancen und Risiken - Marco Caliendo; Alexander S. Kritikos (Institute for the Study of Labor (IZA), 2007)
Support schemes for unemployed aiming for self-employment have been recently reformed several times. In 2003, the start-up subsidy was added to the existing bridging allowance. In 2006 both instruments were merged to the Gründungszuschuss. Since the bridging allowance has been evaluated as effective and efficient and the start-up subsidy reached new target groups, the latest reform shows several shortcomings. The design of the Gründungszuschuss is suboptimal, leading to efficiency losses if its participants act rational. It will also be less effective when compared to the two old programs. Overall, the recent dynamic development of new businesses will slow down more than necessary.
Keywords: 330; Start-up subsidies; active labour market policy; unemployment; Arbeitsmarktpolitik; Arbeitslosigkeit; Unternehmensgründung; Selbstständige; Subvention; Wirkungsanalyse; Deutschland